PENGARUH PERMAINAN BALOK SUSUN TERHADAP PERKEMBANGAN ANAK STUNTING USIA 1-3 TAHUN DI DESA SIGAR PENJALIN LOMBOK UTARA - Endah Sulistyani; Lalu Andriadi; Nurhayati (PrimA: Jurnal Ilmiah Ilmu Kesehatan, 2024)
Abstract The government launched a National Action Plan for Stunting Management in August 2017,which emphasizes convergence activities at the national,regional,and village levels. These activities prioritize specific nutrition and sensitive nutrition intervention in the first 1,000 days of life up to the age of 6 years. Sigar Penjalin Village is one of the locations with stunting cases in North Lombok Regency The data indicates that there are  33%  of children who are stunted in Sigar Penjalin Village.Asprospective nurses, the researchers provide education through playing building Blocks. Objective: The aims of this study is to determine the effect of the stacking lock game on the development of stunted children aged 1-3 years in Sigar Penjalin Village North Lombok. Method: This study was quantitative approach with a pre-experimental design method, specificallythe one-group pre-test post-test design. The sample size consists of 34 respondents, selected through purposive sampling technique. The instrurment used to measure progress is the KPSP questionnaire. Preand post-test results were analyzed using paired sample T-Test.The results of the study before being given building blocks playing therapy with doubtful development were as many as 21 people (59%), after being given building blocks playing therapy with appropriate developments  many as 34 people (100%). The study findings reveal a significant positive effect of building blocks on the development of stunted children aged 1-3 years in Sigar  Penjalin Village, North Lombok.Conclusion, the Building Blocks game, conducted over 7 sessions, can effectively enhance the development of children aged 1-3 years who experience stunting, helping children who initially displayed delayed development to catch up to their peers according to their age.